Effect of Early Planting on Soybean Yield: 2023 Growing Season - Eric Adee; Scott Dooley; Mehraj Dar; Vaishali Sharda (Kansas Agricultural Experiment Station Research Reports, 2024)
In an effort to increase soybean yield potential, early planting dates have been promoted as a management practice that can increase yield of soybeans. Early planting of soybeans can be a relative term, meaning late April/early May for some soybean producers in Kansas, but this study’s definition of early planted soybeans is late March/early April. Theoretically, the earlier planting date could allow for more vegetative growth and interception of more light before blooming, increasing the yield potential. With the improvement of soybean seed treatments to protect seed when emergence is slowed due to cool and wet conditions, the early planting may be a viable option. The planting dates in the three years of the study have shown soybean yields as either stable or increased when planting in late March/early April compared to planting in mid-to-late April and early-to-mid May.
Keywords: soybean; planting date; early planting